Salivary Gland Neoplasms, A Clinicopathological Study (Mustansiria Dental Journal, 2018)
A salivary gland tumor is an uncontrolled growth of cells that originates in one of the many saliva-producing glands in the mouth. The salivary glands are afflicted by a greater variety of neoplasms than any other organ system in the body. The objective of this study was to find the most common age group, sex affected, location, and types of salivary gland tumors in Erbil City.A retrospective analysis was done for all the cases of salivary gland tumors received, in the Department of Histopathology, Rizgari Teaching Hospital, for the years 2006, 2007 and 2008, and four histopathological laboratories in different area of Erbil City. All the cases were analyzed for age, sex, site, and type of the tumor, the slides of all cases under the study were re-examined for the histopathological presence or absence of any invasion.The number of the salivary gland tumors was (44) case. The age range of the patients was from (15-69) years, with a mean age of (42.05) years for the males, and (41.54) years for the females. The highest number of patients was seen above (54) years. The total male to female ratio was 0.76:1. Most of the salivary gland tumors were seen associated with the parotid gland and (31.82%) was seen within the age group (28-40) years. Histopathological study showed that the most common benign tumor was pleomorphic adenoma followed by Warthin’s tumor, and the most common malignant tumor was adenoid cystic carcinoma and mucoepidermoid carcinoma. Statistical analysis showed no significant differences present between the benign and the malignant tumor regarding the age, sex, and the invasion.The highest number of patients with salivary gland tumors was seen above (54) years. The total male to female ratio was 0.76:1. Most of the salivary gland tumors were seen associated with the parotid gland .The most common benign tumor was pleomorphic adenoma followed by Warthin’s tumor, and the most common malignant tumor was adenoid cystic carcinoma and mucoepidermoid carcinoma.